2018
DOI: 10.3126/jpahs.v5i1.24041
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth at Patan Hospital, Nepal

Abstract: Introductions: Stillbirth (SB) is one of the most common adverse outcomes of pregnancy. The aim of this study was to determine the SB rate and to identify the likely causes contributing to SB. Methods: This cross-sectional study was conducted at Patan Hospital from 15th June 2014 to 14th June 2017 for all the cases of SBs, at or after 22 weeks, birth weight of 500 gm or more. The perinatal outcome, demographic profile, fetal characteristics, causes and contributing factors were analyzed. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[Table -6] Three studies have mentioned the condition of stillborn foetuses at birth. In the studies conducted by Sharma et al 2 , Shrestha et al 12 and Basaula et al 13 58.2%, 81.3% and 82 % of foetuses were macerated, respectively. The remaining 41.8%, 18.7% and 18% of the foetuses were fresh stillbirths in the same studies respectively.…”
Section: (324%) [Table-5] Sex and The Condition Of The Stillborn Babiesmentioning
confidence: 92%
See 1 more Smart Citation
“…[Table -6] Three studies have mentioned the condition of stillborn foetuses at birth. In the studies conducted by Sharma et al 2 , Shrestha et al 12 and Basaula et al 13 58.2%, 81.3% and 82 % of foetuses were macerated, respectively. The remaining 41.8%, 18.7% and 18% of the foetuses were fresh stillbirths in the same studies respectively.…”
Section: (324%) [Table-5] Sex and The Condition Of The Stillborn Babiesmentioning
confidence: 92%
“…The rate of stillbirth from selected studies reported that the incidence of stillbirth varied from the lowest 8 per 1000 births to highest 23.87 per 1000 births. [2][3][4][5][6][7][8][9][10][11][12][13] The study conducted by Sharma et al 2 reported that the rate of stillbirth was 15 per 1000 births However, the rate was found to be 1.79% in the study conducted by Tamrakar et al 4 Similarly, the rate of stillbirth was 14.83 and 22 per 1000 births in the studies carried out by Thakur et al 6 and Shrestha et al 7 respectively. The incidence of stillbirth was found to be 17.6 per 1000 deliveries in the study carried out by KC et al 8 The rate of antepartum stillbirth was found to be 13.6 per 1000 births in the study conducted by KC et al 10 Likewise, the rate of stillbirth was found to be 11.24 per 1000 births in a study conducted by Shrestha et al 12…”
Section: Incidence Of Stillbirthmentioning
confidence: 97%